Analisis Penerapan Pendekatan dan Model Pembelajaran Mata Pelajaran Bahasa Indonesia di Kelas IV Sekolah Dasar - Annisa Aulia; Annisa Aulia Rahmadita; Azlia Anugerah Putri; Fira Sekarani; Nuralifah Zakiyyah; Tia Rahmania; Mayarni Mayarni (Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The purpose of this research is to analyze the implementation of approaches and learning models in the Indonesian language subject at the Elementary School level. The subjects of this study are fourth-grade teachers in several public elementary schools located in Jakarta. The research employs a qualitative descriptive method through techniques such as interviews, observations, and literature reviews (library research). The findings of the study reveal that many teachers use contextual approaches and the Problem-Based Learning (PBL) model in teaching Indonesian language in the classroom. This is because these approaches and models are considered more suitable for the current development and needs of students.